The Inner Conflict of the Main Character in the Novel Secuil Hati Wanita di Teluk Eden by Vanny Chrisma) - Markub Markub; Iib Marzuqi; Ella Nuraini; Midlazus Zaman Ahmadi; Ahmad Fajrul; Sindi Rahayu (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2020)
A novel of Secuil Hati Wanita di Teluk Eden by Vanny Chrisma W. is a literary work with religious nuances that can provide an interesting experience for living everyday life. This novel has an inner conflict experienced by the main character, so that the novel is studied with the study of literary psychology. This study reveals how the inner conflict experienced by the main character in the form of sadness, hatred, fear and how the main character's efforts in overcoming conflict in the novel Secuil Hati Wanita di Teluk Eden by Vanny Chrisma W. This study uses a literary psychology approach with descriptive analysis method. This method is carried out by presenting a description of the facts that exist in literary works, and followed by an analysis of these facts. The result of this research is the inner conflict experienced by the main character Dela Eden. The life he lived made his mind shaken. There are three classifications of emotions as a result of the inner conflict they experience, namely sadness, hatred and fear. The journey of life that he faced made him very sad. Since her husband was appointed as the leader of the pirates, the main character feels conflicted every time. Because suddenly the husband's attitude changed to be rude, cruel and arbitrary. The efforts made by the main character in overcoming the inner conflict experienced by the main character is to always draw closer to God. The main character in overcoming inner conflict by rebelling is always against the will of her husband who he thinks is not in accordance with what he knows and understands.